Pengaruh Senam Dismenorea Terhadap Penurunan Dismenorea Siswi SMP Negeri 23 Bandar Lampung - Destiana Arabel; Rita Riyanti Kusumadewi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: Adolescence is a dynamic developmental phase in a person's life. One of the biological signs of youth is the start of menstruation by teenagers. Many young women experience menstrual problems, one of which is dysmenorrhoea. Dysmenorrhea is caused by increased production of endometrial alpha prostaglandin, resulting in dysrhythmic uterine contractions and increased uterine muscle tone which results in uterine ischemia. Dysmenorrhea treatment can be done using pharmacological and non-pharmacological methods. Pharmacologically, menstrual pain can be treated with medication. Meanwhile, non-pharmacologically, menstrual pain can be treated with dysmenorrhoea exercises Objective: This study aims to determine the effect of dysmenorrhea exercise on dysmenorrhea in young women at junior high school 23 Bandar Lampung. Method: Pre-experiment with one group pretest – posttest design, technique simple random sampling, sample of 26 teenagers, questionnaire instrument Numeric Rating Scale and Wilcoxon test. Research result: Before carrying out the Dysmenorrhea exercise, all respondents experienced pain which was quite disruptive to their activities during Dysmenorrhea, whereas after implementing the Dysmenorrhea exercise, the majority of respondents experienced a decrease in the level of pain. Test results Wilcoxon shows the Asymp value. Sig. (2-tailed) value <0.05, which means there is an influence of Dysmenorrhea Exercise on reducing Dysmenorrhea pain in young women. Conclusion: There is an effect of dysmenorrhea gymnastics on dysmenorrhea in adolescent girls.